Screening for the efficacy of botanicals and soaps in controlling the Banana Aphid Pentalonia nigronervosa (Hemiptera: Aphididae) under laboratory and screenhouse conditions - Ogwal, Geofrey; Peter Wasswa; Ocimati, Walter; Omondi, Bonaventure Aman; Tazuba, Anthony Fredrick; Otim, Michael Hilary; Blomme, Guy (MDPI, 2026)
Controlling banana aphid (Pentalonia nigronervosa) vectors of banana bunchy-top disease is crucial for integrated disease management. Synthetic insecticides, though effective in aphid control, pose health and environmental risks. Biorational pesticides (including botanicals and soaps) are safer alternatives. This study screened four fresh and fermented aqueous plant extracts (chili pepper, garlic, neem, and peppermint) and three soaps (bathing, laundry bar, and liquid soap) singly or in mixtures against banana aphids through in vitro and in vivo experiments. Aphid-inoculated banana leaf-blade disks were used for the in vitro studies over 96 h. Potted plantlets were used for the in vivo studies over eight weeks. Applying these preparations resulted in significant (p ≤ 0.05) aphid mortality (28.6 to 100%) compared to the water control (3.3%) at 96 h post-spray (hps). In vitro, a single application of nimbecidine® (Azadirachtin 0.03%), garlic, chili-pepper botanicals, insecticidal, and bathing soap caused >50% mortality at 96 hps. Mixed applications of chili pepper, garlic-based, and neem botanicals with soap caused >70% mortality at 96 hps in vitro. Binary mixtures of neem oil, garlic, fermented garlic, or fermented peppermint with insecticidal soap, and neem oil with bar soap, were promising in vivo, reducing the aphid populations to 200 aphids after week 8. However, these potential preparations incurred a higher cost (USD 1.30/banana mat) compared to the synthetic pesticide (USD 0.022/mat). Thus, biorational mixtures have a potential to effectively control banana aphids.